PENGARUH TECHNICAL QUALITY, FUNCTIONAL QUALITY, PERSEPSI HARGA, DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN (STUDI EMPIRIS KONSUMEN PERUM DAMRI CABANG SEMARANG) - Maya Dewi Utami, 10.05.51.0130; Soliha, Euis (Students Journal of Economic and Management, 2014)
DAMRI is one of the state-owned company engaged in the business of land transportation services. DAMRI an alternative to the problem of road transport. The main problem as a land transport agency services that many of its competitors. Therefore, Perum DAMRI Semarang required to always maintain consumer confidence by improving service quality in order to increase consumer satisfaction. Problems on Damri Corporation is a decrease in the level of customer satisfaction with services in Perum DAMRI new branch as evidenced by the increasing number of customer complaints and decreased customer. Based on the results prasurvey, most of the passengers were not satisfied with the bus service Damri. Factors thought to influence the customers dissatisfaction is a physical evidence, price perception and image of the company. The purpose of this study was to analyze the influence of the physical evidence, price perception and corporate image on customer satisfaction transport services Damri Corporation. The population in this study is the customers who use the services of the DAMRI new branch. The sample used in this study were 89 customers Perum DAMRI new branch who have used the service bus DAMRI more than two times. Sampling was done by purposive sampling method. The data used are primary data through questionnaires. The analysis technique used is multiple linear regression analysis. According to analysis done can be seen that the technical quality, functional quality,, price perception and image positive effect on customer satisfaction transport services Damri Corporation. F test results also suggested that the regression model the technical quality, functional quality, price perception and corporate image on customer satisfaction otherwise good. From the analysis koefien determination, technical quality, functional quality, perception of price and image of the company is able to influence customer satisfaction Damri Corporation transport services by 79%.Keywords: technical quality, functional quality, price perception, corporate image, customer satisfaction.